ESTRO ACROP guidelines for target volume definition in the thoracic radiation treatment of small cell lung cancer. (November 2020) - Le Pechoux, Cecile; Faivre-Finn, Corinne; Ramella, Sara; McDonald, Fiona; Manapov, Farkhad; Putora, Paul Martin; Slotman, Ben; De Ruysscher, Dirk; Ricardi, Umberto; Geets, Xavier; Belderbos, José; Pöttgen, Christoph; et al.
Highlights: Thoracic target volume definition in small cell lung cancer (SCLC) can be quite challenging. Addressed through different clinical scenarios: concomitant chemoradiotherapy (CRT) starting on cycle1, concomitant CRT starting after induction chemotherapy or sequential chemoradiotherapy or post-operative radiotherapy in stages I-III SCLC and consolidation thoracic radiotherapy in stage IV. Possible role of stereotactic radiotherapy in early SCLC. In case of induction chemotherapy, given prior to starting RT, reduced volume SCLC primary tumour volume (post CT GTVp) should be considered whereas pre-chemotherapy nodal extent should be considered for nodal disease (pre CT GTVn). Abstract: Radiotherapy (RT) plays a major role in the treatment of small cell lung cancer (SCLC). Therefore, the ACROP committee was asked by ESTRO to provide recommendations on target volume delineation for standard clinical scenarios in definitive (chemo)-radiotherapy (CRT), adjuvant RT for stages I-III SCLC and consolidation thoracic RT for stage IV disease. The aim of these guidelines is to standardise and optimise the process of RT treatment planning for clinical practice and prospective studies. The process for the development of the guidelines included the evaluation of a structured questionnaire followed by a consensus discussion, voting and writing process within the committee. Firstly, we provide recommendations for both the imaging to be performed as part of the diagnostic work-up and for the RT planning process. Secondly, recommendations are made for target volume delineation including delineation of the primary gross tumour volume (GTV) and lymph node GTV and clinical tumour volume (CTV) expansion in the context of definitive and adjuvant RT. With regard to internal target volume (ITV) and planning target volume (PTV) definitions, we make recommendations about the management of geometric uncertainties and target motion. Finally, we provide our opinions on organ at risk (OAR) delineation and organisational issues to be considered.